Studi Komparatif Fatwa MUI dan LBMNU Jawa Timur tentang Kehalalan Karmin sebagai Bahan Tambahan Pangan - Romadhoni, Faishal Akbar; Zakaria, Soni; Afianto, Ahda Bina (Institut Agama Islam Negeri Kerinci, 2024)
The differing opinions on the halal status of carmine between the Indonesian Ulema Council (MUI) and the East Java Bahtsul Masail Nahdlatul Ulama (LBMNU) have raised questions regarding the ijtihad methodologies employed by these two institutions. This study aims to examine the differences in methodology, legal reasoning, and Islamic jurisprudential approaches utilized by the two institutions in determining the halal status of carmine. The research employs a qualitative method with a descriptive-comparative approach, based on an analysis of fatwa documents and relevant literature. The findings indicate that MUI declares carmine halal through a tahqiqul manath approach, incorporating empirical research and considerations of utility, whereas LBMNU prohibits carmine using a textual approach that bases its decision on the impurity of insect carcasses according to the Syafi'i school of thought. These differences suggest that MUI adopts a more adaptive stance toward modern contexts by integrating scientific aspects, while LBMNU prioritizes preserving the tradition of the Syafi'i school. This study underscores the importance of balancing methodological flexibility and adherence to traditional jurisprudence in addressing contemporary challenges.